Study on Static Strain Aging Kinetics of High-Carbon Steel Wires and Its Impact on High-Strength Steel Cords - Tamás Bálint Mező (MDPI AG, 2021)
Under quasi-static loading, an irregular failure mode of high-strength thin carbon steel cords were observed after low-temperature thermal aging. Character and kinetics of damage in such wire ropes highly depend on the plastic elongation of the steel wires, which is significantly modified by the strain aging effect. In this paper, the static strain aging effect on heavily drawn high-carbon steel wires and their cords is experimentally studied in the 80–200 °C temperature range. The kinetics of the aging process is studied in detail. Experimental data are fit by the Johnson–Mehl–Avrami–Kolmogorov (JMAK) kinetic model. The temperature dependence of the static strain aging process is given by means of the Arrhenius equation. The associated JMAK exponents, the apparent activation energy and the pre-exponential constant are determined. Quantitative analysis of the affected strength and strain parameters is given, and based on this, the macroscopic failure mechanism is fundamentally explained.